Association of Mouse Mammary Tumor Virus With Human Breast Cancer: Histology, Immunohistochemistry and Polymerase Chain Reaction Analyses - Lawson, James S.; Mazzanti, Chiara; Civita, Prospero; Menicagli, Michele; Ngan, Christopher C.; Whitaker, Noel J.; Hochman, Jacob; Braitbard, Ori; Yosufi, Benafsha; Glenn, Wendy K. (Frontiers in Oncology, 2018)
Purpose. The purpose of this study is to determine whether mouse mammary tumour virus (MMTV) associated human breast cancer has the same or similar histology to MMTV associated mouse mammary tumours. Such associations may indicate a role for MMTV in human breast cancer. Methods. Immunohistochemical techniques (using antibodies directed against the signal peptide p14 of the envelope precursor protein of MMTV) and polymerase chain reaction (PCR) analyses were used to identify MMTV proteins and MMTV-like envelope gene sequences in a series of breast cancers from Australian women. The histological characteristics of these human breast cancer specimens were compared with MMTV positive mouse mammary tumours. The same methods were used to study benign breast tissues which 1 to 11 years later developed into breast cancer. Results. MMTV p14 proteins were identified in 27 (54%) of 50 human breast cancers. MMTV env gene sequences were identified by PCR in 12 (27%) of 45 human breast cancers. There was a significant correlation between the presence of MMTV (identified by p14 immunohistochemistry) in human breast cancers and histological characteristics similar to MMTV positive mouse mammary tumours (p= 0.001). There was a non-significant correlation between the presence of MMTV env gene sequences (identified by PCR) in human breast cancers and histological characteristics similar to MMTV positive mouse mammary tumours (p= 0.290). MMTV p14 proteins were identified in 7 (54%) of 13 benign breast specimens that later developed into human breast cancers. MMTV by PCR was identified in 2 benign specimens one of whom later developed MMTV positive breast cancer. Discussion. These observations offer evidence that MMTV may be associated with characteristic human breast cancer histology. p14 based immunohistochemistry appears to be a more reliable technique than PCR for the identification of MMTV in human breast cancer. Identification of MMTV associated p14 proteins in benign breast tissues confirms prior PCR based studies that MMTV infection occurs before the development of MMTV positive breast cancer. Conclusion. Many MMTV positive human breast cancers have similar histology to MMTV positive mouse mammary tumours. MMTV infection identified in benign breast tissues precedes development of MMTV positive human breast cancer. When